Bridging continual reassessment method for phase I clinical trials in different ethnic populations. (28th January 2015) - Liu, Suyu; Pan, Haitao; Xia, Jielai; Huang, Qin; Yuan, Ying
<x xml:space="preserve">Abstract</x> Accumulating evidence shows that the conventional one‐size‐fits‐all dose‐finding paradigm is problematic when applied to different ethnic populations. Because of inter‐ethnic heterogeneity, the dosage established in a landmark trial for a certain population may not be generalizable to a different ethnic population, and a follow‐up bridge trial is often needed to find the maximum tolerated dose for the new population. We propose the bridging continual reassessment method (B‐CRM) to facilitate dose finding for such follow‐up bridge trials. The B‐CRM borrows information from the landmark trial through a novel estimate of the dose‐toxicity curve and accommodates the inter‐ethnic heterogeneity using the Bayesian model averaging approach. Extensive simulation studies show that the B‐CRM has desirable operating characteristics with a high probability to select the target dose. This article focuses on ethnic heterogeneity, but the proposed method can be directly used to handle other types of patient heterogeneity, for example, patient subgroups defined by prognostic factors or biomarkers. The software to implement the B‐CRM design is available for free download at http://odin.mdacc.tmc.edu/ yyuan/. Copyright © 2015 John Wiley & Sons, Ltd.